2019
DOI: 10.3389/fnins.2019.00701
|View full text |Cite
|
Sign up to set email alerts
|

An MRI Study of Neurovascular Restorative After Combination Treatment With Xiaoshuan Enteric-Coated Capsule and Enriched Environment in Rats After Stroke

Abstract: Xiaoshuan enteric-coated capsule (XSEC) is a Chinese medicinal compound widely used for treatment of ischemic cerebrovascular diseases. Enriched environment (EE) is an effective rehabilitative protocol designed to enhance sensorimotor, cognitive and social stimulation. This study aimed to apply magnetic resonance imaging (MRI) to non-invasively assess whether EE could augment the therapeutic benefits of XSEC on post-ischemic neurovascular remodeling. Male Sprague–Dawley rats were subjected to perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Thus, there is a positive correlation between Ang II and VEGF in angiogenesis. It is suggested that Ang II may upregulate the expression of VEGF through AT1R signal transduction pathway to promote angiogenesis ( Zhan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a positive correlation between Ang II and VEGF in angiogenesis. It is suggested that Ang II may upregulate the expression of VEGF through AT1R signal transduction pathway to promote angiogenesis ( Zhan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is an intricate biological process regulated by various angiogenic growth factors, which are crucial in the mutual communication between endothelial cells and pericytes during the angiogenesis process [6]. VEGF is the most prominent member of the angiogenic growth factors, playing a critical role in the migration [48], proliferation [49], and tube formation of endothelial cells [50].…”
Section: Angiogenesismentioning
confidence: 99%
“…VEGF is the most prominent member of the angiogenic growth factors, playing a critical role in the migration [48], proliferation [49], and tube formation of endothelial cells [50]. Previous studies have shown that Ang-1 and Ang-2 depend on VEGF to modulate angiogenesis [6]. Ang-1, as a paracrine signal [51] derived from pericyte [52], is essential for vessel maturation and stabilization [53].…”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, standard descriptors do not exploit the full information content of synthetic data generated from the models. At the same time, advances in imaging technology mean that it is now possible to visualize vascular architectures across multiple spatial scales [ 37 ]. These imaging developments are creating a need for new methods that can quantify the multi-scale patterns in vascular networks, and how they change over time.…”
Section: Introductionmentioning
confidence: 99%